Pelaksanaan Pendidikan di Sekolah Dasar dalam Perkembangan Teknologi - Messiana Jayati; Yari Dwikurnaningsih; Sophia Tri Satyawati (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2025)
The development of technology has brought significant changes in various aspects of life, including basic education. This study examines the implementation and perception of technology utilization in learning in primary schools, its positive and negative impacts, and the important role of schools and parents in guiding students. The survey results show that the majority of primary schools have integrated technology in the teaching-learning process, such as the use of PowerPoint and projectors, which are proven to increase students' interest and enthusiasm. Educators and school principals realize the need to adapt teaching methods to suit technological developments, so that students are not only passive consumers, but also able to utilize technology effectively and wisely. While technology offers easy access to information, interactive learning and administrative efficiency, there are also challenges such as the potential for decreased focus, the digital divide, as well as data security issues and the spread of inaccurate information. Therefore, instilling values of wisdom, ethics and responsibility in the use of technology is crucial. Collaboration between schools and parents is needed to equip students with the ability to sort out information and avoid the negative impacts of technology, in order to create a smart and responsible generation in the digital era.